2008
DOI: 10.1021/cg700656r
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Change of Calcium Carbonate in the Presence of Polynucleotides

Abstract: Two-dimensional DNA lattices are grown under conditions that also are suitable for the magnesium-free growth of three-dimensional calcium carbonate crystals. These lattices are used to template morphology changes in calcium carbonate. The effects of DNA lattices, sub-assemblies, duplexes, single strands, dinucleotides, and mononucleotides on calcium carbonate morphology are studied. A "rotated" morphology of calcite is found to predominate when a critical concentration of any polynucleotide is reached in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Examples of successful aptamer–inorganic material interfaces are most prevalent in metal and semiconductor nanoparticle conjugation ,, but also in DNA-templated metal nanoparticle synthesis. ,, The preparation and understanding of ionic solids through precipitation, mineralization, or biomineralization reactions are of particular interest due to biomedical, biogenic, and environmental applications. Ionic solids are particularly amenable to interactions with DNA due to the possibility of strong electrostatic interactions and divalent cation chelation. DNA–mineral interactions have been demonstrated computationally, through binding affinity experiments, and through the beautiful mineralization of DNA origami structures. , The SELEX (Systematic Evolution of Ligands by EXponential enrichment) identification of DNA aptamers specifically capable of mineralizing ionic materials was recently reported by Bawazer et al, who completed an affinity binding-based selection, and by Baillargeon et al, who introduced a precipitation selection method. In Precipitation SELEX, a library of DNA aptamers is combined with precursor ions, specifically calcium and phosphate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of successful aptamer–inorganic material interfaces are most prevalent in metal and semiconductor nanoparticle conjugation ,, but also in DNA-templated metal nanoparticle synthesis. ,, The preparation and understanding of ionic solids through precipitation, mineralization, or biomineralization reactions are of particular interest due to biomedical, biogenic, and environmental applications. Ionic solids are particularly amenable to interactions with DNA due to the possibility of strong electrostatic interactions and divalent cation chelation. DNA–mineral interactions have been demonstrated computationally, through binding affinity experiments, and through the beautiful mineralization of DNA origami structures. , The SELEX (Systematic Evolution of Ligands by EXponential enrichment) identification of DNA aptamers specifically capable of mineralizing ionic materials was recently reported by Bawazer et al, who completed an affinity binding-based selection, and by Baillargeon et al, who introduced a precipitation selection method. In Precipitation SELEX, a library of DNA aptamers is combined with precursor ions, specifically calcium and phosphate.…”
Section: Introductionmentioning
confidence: 99%
“…DNA−mineral interactions have been demonstrated computationally, 17−19 through binding affinity experiments, 20−24 and through the beautiful mineralization of DNA origami structures. 25,26 The SELEX (Systematic Evolution of Ligands by EXponential enrichment) identification of DNA aptamers specifically capable of mineralizing ionic materials was recently reported by Bawazer et al, 27 who completed an affinity binding-based selection, and by Baillargeon et al, 28 who introduced a precipitation selection method. In Precipitation SELEX, 28 a library of DNA aptamers is combined with precursor ions, specifically calcium and phosphate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…During recent years, various biomolecules have been exploited to control the nucleation and growth of inorganic materials and thus manipulate their structures and physical properties. So far, DNA [3], proteins [4], peptides [5,6], virus [7], and some other biomolecules [8][9][10] have been used as structure-directing agents to assist synthesis of inorganic materials. Especially, l-cysteine, a kind of biomolecules with special structure, can serve as sulfur source for the fabrication of metal sulfides.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports showed that the polymorph of calcium carbonate is dependent on the operating conditions of crystallization, such as supersaturation [8], solution composition [9], pH [10], temperature [11], and presence of additives [12][13][14][15][16][17][18][19]. The effect of additives has been studied on the crystallization of calcium carbonate.…”
Section: Introductionmentioning
confidence: 99%